[View of south side of campus from Radio Hill] (1940)
On back: "Dormitory Row - Looking southeast toward Dormitory Row (ca. 1940)". Buildings include natatorium, President's House, and San Luis Obispo residences. Palm trees and California Boulevard are visible.